STATUS UNSUR HARA MAKRO PADA INCEPTISOL YANG DITANAMI PAKCOY (Brassica rapa L.) - Ardli Swardana; Fadila Nurul Iman; Jenal Mutakin (Jurnal Tanah dan Sumberdaya Lahan, 2023)
One of the activities of cultivating pakcoy (Brassica rapa L.) requires soil that has good fertility. One of the important soil fertility parameters for pakcoy plant growth is the availability of macro nutrients. Inceptisol  is a soil that is quite extensive and has the potential to be developed but has problems in soil fertility. The purpose of this study was to determine the macronutrient status of inceptisol planted by pakcoy. The research was conducted in Kertanegla Village, Bojonggambir District, Tasikmalaya Regency, in January-February 2022. The method used in this study was a descriptive quantitative analysis of macro nutrients from soil analysis results. The results showed that the measured value for nitrogen was 0.1%, phosphorus value was 21.00 mg 100 g-1, and potassium was 41.00 mg 100 g-1. Based on these values, the macronutrient status at the study site, namely the nutrient status of nitrogen, was low, phosphorus was medium, and potassium was high.